2020
DOI: 10.1177/1040638720965540
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of an outbreak of highly pathogenic avian influenza A(H5N1) virus of clade 2.3.2.1a in turkeys in Bangladesh

Abstract: A mixed-aged flock of 130 turkeys in Bangladesh reported the sudden death of 1 bird in September 2017. Highly pathogenic avian influenza A(H5N1) virus was detected in 3 turkeys, and phylogenetic analysis placed the viruses in the reassortant clade 2.3.2.1a. The birds had clinical signs of depression, diarrhea, weakness, closed eyes, and finally death. The mortality rate of the flock was 13% over the 6 d prior to the flock being euthanized. At autopsy, we observed congestion in lungs and brain, hemorrhages in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 20 publications
(45 reference statements)
1
7
0
Order By: Relevance
“…This high level of detection of H5 AIV is similar to that observed in Egypt, another enzootic country, where HPAI virus was detected in 62.16% of the farms reporting sudden death or drop in egg production (Artois et al, 2018). In contrast to the field observations, officially Bangladesh reported only six HPAI outbreaks to OIE during 2017-2018, though the continuous circulation of both H5 HPAI and H9 LPAI viruses in live bird markets (Chowdhury et al, 2020;Kim et al, 2018;Turner et al, 2017) and a few clinical outbreaks of HPAI due to H5N1 virus (Mumu et al, 2021;Nooruzzaman, Mumu, et al, 2019) have been reported in the literature.…”
Section: Discussionsupporting
confidence: 77%
“…This high level of detection of H5 AIV is similar to that observed in Egypt, another enzootic country, where HPAI virus was detected in 62.16% of the farms reporting sudden death or drop in egg production (Artois et al, 2018). In contrast to the field observations, officially Bangladesh reported only six HPAI outbreaks to OIE during 2017-2018, though the continuous circulation of both H5 HPAI and H9 LPAI viruses in live bird markets (Chowdhury et al, 2020;Kim et al, 2018;Turner et al, 2017) and a few clinical outbreaks of HPAI due to H5N1 virus (Mumu et al, 2021;Nooruzzaman, Mumu, et al, 2019) have been reported in the literature.…”
Section: Discussionsupporting
confidence: 77%
“…The study also reported that separating new from old birds in the turkey farms significantly reduced the occurrence of AIV, with the odds of AIV as low as 0.1. In a previous study by Mumu et al ( 36 ), a significant percentage of turkey mortality due to HPAI H5N1 outbreak was reported on a turkey farm in Bangladesh where they reared different ages of turkeys in a single shed.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of turkey was random, and no specific characteristics were considered during sampling. We recorded the health status of turkey birds following the selection process and identified the sick birds based on their clinical signs and symptoms ( 36 , 41 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations